Possible Factors Behind Dicrepancies in Export LC Documents: a Survey of ICI-500 Companies in Turkey - kula, veysel (Archives of Business Research, 2015)
Letter of credit (LC) is a frequently used payment mechanism in international trade and is traditionally regarded as the assurance of payment for the exporter. LC process requires exporters to submit to banks documents that are in compliance with the terms of LC. Strict compliance principle mostly results in the rejection of the documents by the banks, thus jeopordazing the collection of the proceeds of the sales by the exporters. Drawn on the data obtained through survey from 460 ICI 500 list companies in Turkey, this study attemts to explore the possible reasons behind the discrepancies in the documents presented by the exporters. Ordered logit regression analysis results indicate that the tendency of importers to waive, as perceived by exporters, to waive discrepancies and the difficulties in complying with sales contract terms have statistically significant positive relationship with the extent of discrepancies. On the other hand, competency of the export personnel results in lesser amount of discrepancy.